PENGARUH TERAPI MUSIK KLASIK TERHADAP TINGKAT STRES PADA LANSIA DI BALAI PELAYANAN SOSIAL TRESNA WERDHA UNIT BUDI LUHUR, BANTUL YOGYAKARTA - Nur Hidayat; Erviandri Leo Bogo (MIKKI (Majalah Ilmu Keperawatan dan Kesehatan Indonesia), 2018)
ABSTRACT Background: Aging is part of the process of growth and development. Humans do not suddenly grow old, but develop from babies, children, adults and eventually grow old. When a person enters old age, he will experience various changes both physical,mental and social   Objective: This study aims to determine the effect of classical music therapy on stress levels in the elderly at the Tresna Wredha Social Services Unit Budi Luhur Unit,Bantul Yogyakarta. Research Method: This study uses (Quasi Experiment) with Pre test research design and post test with Non Equivalent Control Group Design which explains the effect of giving independent variables (classical music therapy) to the dependent variable (decreased stress level). The sampling method uses total sampling. Data analysis used was univariate and bivariate using paired t-testResults: Based on statistical tests using paired t-test results obtained the inﬂ uence of classical music therapy with stress levels in the elderly, with a p-value = (0.000 <0.05)Conclusion: There is an effect of classical music therapy on stress levels in the elderly at the Tresna Werdha Social Services Center Budi Luhur Unit, Bantul Yogyakarta.